THE ROLE OF PHYSICAL CULTURE AND SPORTS IN HUMAN LIFE AND PROFESSIONAL TRAINING OF AN EMPLOYEE OF THE INTERNAL AFFAIRS BODIES (World Bulletin of Social Sciences, 2023)
This article discusses the role and place of physical culture in human life. Its functions are analyzed, highlighting the author's position on some of them. The author also emphasizes the fact that physical culture is not always a long and exhausting workout. Sports can be a part of daily activities and recreation, while having a positive effect on the body. Playing sports allows not only to maintain health and physiological indicators at the proper level, but also to strengthen the psychological side of human life. Physical culture is also an important part of the professional training of law enforcement officers. It is through it that police officers maintain their readiness to perform operational and official tasks, including in situations of real confrontation with offenders.
Keywords: physical culture; sports; classes; exercises